Pengembangan Media Audiovisual Inspirasional sebagai Edukasi Menulis Deskripsi pada Siswa Kelas V SDN 34 Pontianak Selatan - Nurhayati Nurhayati; Siti Halidjah; Dyoty Auliya Vilda Ghasya; Hery Kresnadi; Asmayani Salimi (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
This study aims to develop inspirational audiovisual media as an education for writing descriptions for fifth grade students at SD Negeri 34 Pontianak Selatan. The research method used is the research and development method (RnD) by adapting the Borg and Gall model with potential and problem steps, data collection, product design design validation, design revisions, product trials and product revisions. Quantitative data was obtained from the results of product assessment by the validator and filling out a response questionnaire to the media by students. Qualitative data were obtained from suggestions/comments by validators and students. Research instruments in the form of interviews and questionnaires. The level of validity of the media is based on the results of assessments by media experts and material experts while the response to the media is based on the results of responses by students. The validation results of inspirational audiovisual media obtained an average of 3.55 ''very valid''. Students' responses to inspirational audiovisual media obtained an average of 3.45 ''very good''. Students' practicality of inspirational audiovisual media obtained an average of 3.705 ''very practical''.